2021
DOI: 10.1177/20587384211059675
|View full text |Cite
|
Sign up to set email alerts
|

Early use of canakinumab to prevent mechanical ventilation in select COVID-19 patients: A retrospective, observational analysis

Abstract: Introduction The fully-human monoclonal anti-interleukin (IL)-1β antibody canakinumab may inhibit the production of inflammatory mediators in patients with coronavirus disease 2019 (COVID-19) and the hyperinflammatory response potentially leading to acute respiratory distress syndrome. Objectives The goal of our retrospective, observational analysis was to evaluate the safety and efficacy of subcutaneous (s.c.) canakinumab in combination with our standard of care (SOC) treatment of selected patients with COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…Based on clinical data, the US-CDC recommends against the use of canakinumab for treatment of COVID-19 [ 519 ]. Nevertheless, similar to tocilizumab and antibodies targeting SARS-CoV-2, early use of canakinumab was shown to provide superior efficacy over standard of care [ 536 ]. Similarly, clinical studies on antibodies targeting IL-33R, IL-22, P-selectin, IFN-γ, CTGF, and CD73 to improve COVID-19 outcomes all have been discontinued due to lack of clinical efficacy (Table 10 ).…”
Section: Antibodies For Palliative Therapymentioning
confidence: 99%
“…Based on clinical data, the US-CDC recommends against the use of canakinumab for treatment of COVID-19 [ 519 ]. Nevertheless, similar to tocilizumab and antibodies targeting SARS-CoV-2, early use of canakinumab was shown to provide superior efficacy over standard of care [ 536 ]. Similarly, clinical studies on antibodies targeting IL-33R, IL-22, P-selectin, IFN-γ, CTGF, and CD73 to improve COVID-19 outcomes all have been discontinued due to lack of clinical efficacy (Table 10 ).…”
Section: Antibodies For Palliative Therapymentioning
confidence: 99%
“…Canakinumab showed positive effects on inflammatory markers, oxygen improvement, and final outcomes of COVID-19 patients according to the results of several retrospective studies. 180 183 However, a randomized, double-blind, placebo-controlled phase III study indicated that canakinumab exhibited no benefit on mechanical ventilation requirement and mortality in hospitalized patients with severe COVID-19 (NCT04362813). 184 In addition, Canakinumab has been evaluated in the COVID-19 patients concurrently with cardiac injury or type 2 diabetes, whose results have not been published (NCT04365153, NCT04510493).…”
Section: Pyroptosis and Sars-cov-2mentioning
confidence: 99%
“…After literature search, a total of 6 studies 4 , 5 , 6 , 7 , 8 , 9 comprising of 1121 adult patients with COVID-19, including 379 in the canakinumab (administered alone) and 742 in the control group arm, were included in this meta-analysis. The study characteristics of the included studies are listed in Table 1 .…”
Section: Dear Editormentioning
confidence: 99%